Acyl-Homoserine Lactone Production Is More Common among Plant-Associated Pseudomonas spp. than among Soilborne Pseudomonas spp. - Elasri, Miena (American Society for Microbiology, 2001)
A total of 137 soilborne and plant-associated bacterial strains belonging to different Pseudomonas species were tested for their ability to synthesize N-acyl-homoserine lactones (NAHL). Fifty-four strains synthesized NAHL. Interestingly, NAHL production appears to be more common among plant-associated than among soilborne Pseudomonas spp. Indeed, 40% of the analyzed Pseudomonas syringae strains produced NAHL which were identified most often as the short-chain NAHL, N-hexanoyl-l-homoserine lactone, N-(3-oxo-hexanoyl)-homoserine lactone, and N-(3-oxo-octanoyl)-l-homoserine lactone (no absolute correlation between genomospecies of P. syringae and their ability to produce NAHL could be found). Six strains of fluorescent pseudomonads, belonging to the species P. chlororaphis, P. fluorescens, and P. putida, isolated from the plant rhizosphere produced different types of NAHL. In contrast, none of the strains isolated from soil samples were shown to produce NAHL. The gene encoding the NAHL synthase in P. syringae pv. maculicola was isolated by complementation of an NAHL-deficient Chromobacterium mutant. Sequence analysis revealed the existence of a luxI homologue that we named psmI. This gene is sufficient to confer NAHL synthesis upon its bacterial host and has strong homology to psyI and ahlI, two genes involved in NAHL production in P. syringae pv. tabaci and P. syringae pv. syringae, respectively. We identified another open reading frame that we termed psmR, transcribed convergently in relation to psmI and partly overlapping psmI; this gene encodes a putative LuxR regulatory protein. This gene organization, with luxI and luxR homologues facing each other and overlapping, has been found so far only in the enteric bacteria Erwinia and Pantoea and in the related species P. syringae pv. tabaci.